A Structural Model to Explain Influences of Organisational Communication on the Organisational Commitment of Primary School Staff - John De Nobile; Ayse Aysin Bilgin (MDPI AG, 2022)
Organisational commitment is a job attitude frequently linked to employee morale, motivation and behaviour. High organisational commitment has been associated with increased effort and productivity, while low commitment has been associated with low productivity, absenteeism and turnover. There is evidence to suggest aspects of organisational communication are important in this regard. This article reports the results of a study that investigated the relationships between a comprehensive set of aspects of organisational communication and general organisational commitment, while also identifying those that had the most important effects on organisational commitment. Participants were 1575 staff members from government and non-government primary schools across all states and territories of Australia. Data were gathered using a survey comprising the Organisational Communication in Primary Schools Questionnaire and a five-item general organisational commitment scale. Exploratory and confirmatory factor analyses were used to identify and validate constructs for measurement. Structural equation modelling was used to identify important relationships. Of the ten aspects of organisational communication identified, five had significant effects on general organisational commitment. The most important of these concerned openness between principals and staff, supportive communication among colleagues (positive effects) and communication overload (negative effects). Implications for school leadership and school culture are discussed along with directions for further research.